2018
DOI: 10.1016/j.ymthe.2017.09.024
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β Mediates Renal Fibrosis via the Smad3-Erbb4-IR Long Noncoding RNA Axis

Abstract: Transforming growth factor β (TGF-β)/Smad3 signaling plays a role in tissue fibrosis. We report here that Erbb4-IR is a novel long non-coding RNA (lncRNA) responsible for TGF-β/Smad3-mediated renal fibrosis and is a specific therapeutic target for chronic kidney disease. Erbb4-IR was induced by TGF-β1 via a Smad3-dependent mechanism and was highly upregulated in the fibrotic kidney of mouse unilateral ureteral obstructive nephropathy (UUO). Silencing Erbb4-IR blocked TGF-β1-induced collagen I and alpha-smooth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
140
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(142 citation statements)
references
References 42 publications
(87 reference statements)
2
140
0
Order By: Relevance
“…31 The primary antibodies used in this study included antibodies against Cybernetics, Bethesda, MD) as described previously. 32,33…”
Section: Morphological and Immunohistochemical Analysismentioning
confidence: 99%
“…31 The primary antibodies used in this study included antibodies against Cybernetics, Bethesda, MD) as described previously. 32,33…”
Section: Morphological and Immunohistochemical Analysismentioning
confidence: 99%
“…Lineage tracing suggests that these disease-causative cells arise predominantly from glioma-associated oncogene homolog 1 + -forkhead box (FOX) D1 + vascular pericytes and fibroblasts (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), a conclusion supported by sine oculis homeobox homolog 2 fate mapping of the injured renal epithelium (35,37). TGF-b1 governs the myofibroblastic differentiation of pericytes and resident fibroblasts while coordinating a program of pathologic ECM synthesis and advancing fibrosis (38)(39)(40)(41)(42)(43)(44). Indeed, mice engineered to express epithelial-targeted, inducible, constitutively active TGF-b receptor I exhibit acute tubular injury and apoptosis, phenotypic dedifferentiation, synthesis of profibrotic factors, and interstitial inflammatory cell recruitment (45).…”
Section: The Renal Fibrotic Microenvironmentmentioning
confidence: 96%
“…; Feng et al . ). These studies revealed that lncRNA may serve as a competing endogenous RNA (ceRNA) or a molecular sponge for modulating the expression and biological functions of miRNAs.…”
Section: Introductionmentioning
confidence: 97%
“…; Feng et al . ), but platforms specific for lncRNA interactions with other biomolecules are still not available.…”
Section: Introductionmentioning
confidence: 99%